Mineral resources and energy : future stakes in energy transition - Vidal, Olivier (ISTE Press Ltd, 2018)
"Increasing the world's population to 9 billion by 2050 will lead to an increase in the need for raw materials that support basic human activities, as well as all developments in new technologies, mobility, energy. If current trends continue, projections indicate that to meet global needs by 2050, we will have to extract more metals from the subsoil than mankind has extracted since the inception. It is against this backdrop of strong demand for metals that energy and the transition to decarbonized energy production arise. The stakes associated with energy and mineral raw materials are indissociable because metals are necessary to build the infrastructures of production of energy, its storage and its distribution, but also because the energy is necessary to produce the raw materials. The offshoring of production weighs on the adaptive capacities of Western non-producing countries, which are currently confronted with the economic, political and technological emergence of producer countries such as China. Industries in developed non-producing countries are thus placed in a situation of great dependence on imports of fossil energy, but also mineral resources. In this highly competitive context, the stakes in raw materials and energy are considerable. Mineral Resources and Energy addresses these topics from the point-of-view of needs, notably to ensure the energy transition and primary production, recycling, technological innovation, economic and social issues. A chapter is devoted to modeling in order to understand and integrate these couplings in a global model. Increasing the world's population to 9 billion by 2050 will lead to an increase in the need for raw materials that support basic human activities. In this highly competitive context, the stakes in raw materials and energy are considerable. This book addresses these needs in order to ensure energy transition, primary production, recycling and technological innovation. Approaches the issues of commodities and energy in terms of needs, technological innovation and economic and social issues Emphasizes the couplings between these different aspectsHelps readers understand and integrate these couplings through global modeling"--